Effect of empowering leadership on employees’ workplace loneliness: a moderated mediation model - Hou, Lingyan; Cai, Wenjing (Frontiers in Psychology, 2024)
Workplace loneliness has become a prevalent experience among employees in organizations; however, there is limited empirical research on how leaders can address and mitigate this issue. Drawing upon self-determination theory and empowering leadership theory, this study examines the impact of empowering leadership on workplace loneliness by exploring the mediator of role breadth self-efficacy and the moderator of leader–member conversational quality. A time-lagged research design was used, collecting data through a two-wave online survey involving 531 employees in Chinese public sectors. The participants consisted of 321 males and 210 females, with an average age of 35 years (SD = 7.36). Our findings indicate that empowering leadership positively influences employees’ role breadth self-efficacy, reducing their workplace loneliness. Moreover, leader-member conversational quality strengthens this indirect effect, suggesting that empowering leadership is more effective in reducing workplace loneliness when leader-member conversational quality is high. This study expands and enriches research on the antecedents of workplace loneliness from the leadership approach, providing valuable insights for organizations to implement interventions that effectively alleviate employees’ workplace loneliness.